Awareness of Screening and Prevention of Cervical Cancer in Women of Reproductive Age Group: The Overlooked Entities! - Patil, Kartik Sudhakar; Kulkarni, Meenal V (National Journal of Community Medicine, 2016)
Background: India carries the leading cancer load for cervical cancer, however, awareness regarding cervical cancer is poor among women of reproductive age group. The study was conducted with objectives to find out awareness regarding cervical cancer among women of reproductive age group from urban slum; and to assess screening and preventive practices and reasons for non screening . Methods: A Cross sectional study was carried out in an urban slum. Total of 200 women of age group 15-50 years were interviewed with a pretested preformed questionnaire. Result: General awareness about cervical cancer was about 42%. The knowledge of cervical cancer regarding causative agent, risk factors, cardinal symptoms and preventive measures was found to be poor. Only 6(3%) were aware of Pap test and only 2 (1%) of the women had ever undergone screening in their life. Main reasons for non-screening were lack of knowledge. Only 4.5% women were aware about HPV vaccine and none had ever taken. Conclusion: Level of knowledge regarding cervical cancer screening and prevention was found to be poor. Screening practices were negligible & none of them ever vaccinated with HPV vaccine. Lack of knowledge was the main reason for non screening.